Improving the Reading Skills of a Students with Reading Difficulties: An Action Research - Kayabasi, Zehra Esra Ketenoglu; Akyol, Hayati̇ (Turkish Education Association, 2018)
In this study, it was aimed to remediate the reading and reading comprehension problems of a third grade elementary school student. The study employed action research design, which is among qualitative research methods. The student was included in the study on the basis of having no mental, visual and audial problem. In the study, it was primarily diagnosed that the student was at the anxiety level after applying a pre-test “Error Analysis Inventory”, “Texts”, “Oral Reading Records” and “Researcher Journals and Observations” were used as data collection tools. It was seen that the student could not read the texts fluently, made spelling errors, additions, misreading, and skipping. An individualized reading program was developed based on the student’s reading skills. This program included 30 hour lessons (one hour for each lesson) and divided into two parts. In the first part of the training program, phonics, syllables and words were emphasized for 15 hours. The student, at the same time, was allowed to write the syllables and words she had learned in this process. Reading fluency of the student was tried to be improved in the second part of the study for 15 hours. Appropriate texts were selected from the lower grade for the student in this process. Reading skills of the student were developed by using the “Paired Reading” and “Repetitive Reading” methods. At the end of the study, a post-test was administered by the researchers and it was determined that the reading and comprehension levels of the student advanced from anxiety level to teaching level.
Keywords: Reading, Comprehension, Reading difficulty, Repetitive reading, Paired reading; Okuma, Anlama, Okuma güçlüğü, Tekrarlı okuma, Eşli okuma; 4. Education